Removal of Oil Waste by iron oxide Biochar Prepared from Sugarcane Bagasse - Pushpa, Pushpa latha A/P Subramaniam (Progress in Engineering Application and Technology, 2021)
Nowadays, the dissolution of microsized oil droplets from water is stronglyrequired by the environmental protection. Oil pollution has become a severeenvironmental issue and has attracted global concern. However, the oil released fromhousehold activities particularly cooking and bathing, could contaminate thesurrounding environment and human health. The presence of contaminants in oilwaste raises concerns as small quantities of organic chemicals have been shown to becarcinogenic to mammals and can pose a risk to both human health and aquaticorganisms. Therefore, the presents study investigated the performance of iron oxidesugarcane bagasse biochar in the removal of oil waste from aqueous solution. Theiron oxide sugarcane bagasse biochar is produced using co-precipitation method ofiron chloride (FeCl3) and iron sulphate (FeSO4). Then, the magnetic biochar ischaracterized by Fourier Transform Infrared Spectroscopy (FTIR) and ScanningElectron Microscope (SEM). The efficiency of the magnetic biochar in removing oilwaste are measured by performed a batch experiment with different iron oxidebiochar dosages, oil waste concentration and contact time. At the end of theexperiment, the iron oxide sugarcane bagasse biochar is separated by using a magnet.The optimum performance condition of the iron oxide sugarcane biochar is thenundergone three cycles of adsorption process to determine the adsorption capacity.From the results of the adsorption experiment, the optimum separation of oil wastewas achieved when contact with 0.25% concentration of oil,1.5g of magneticsugarcane bagasse biochar at 120 seconds with separation efficiency of 99%. Afterperformed three cycle of adsorption process, the iron oxide biochar still showing anexcellence removing performance which towards zero waste production could beachieved. The findings constitute that the iron oxide sugarcane bagasse biochar isefficient to be used in removal of waste cooking oil from aqueous solution. Thus, theprospect of iron oxide biochar utilization is promising as it is can customized forspecific environmental applications.